Knowledge as property issues in the moral grounding of intellectual property rights - Chandra, Rajshree (New Delhi ; Oxford : Oxford University Press, 2010)
Using philosophical, empirical, and theoretical approaches, this inquiry into the nature and scope of Intellectual Property Rights (IPRs) studies the different justifications usually put forward in favour of protecting rights in intellectual property and shows how such rights come into conflict with other rights in society.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Intellectual property